2013
DOI: 10.5694/mja12.10929
|View full text |Cite
|
Sign up to set email alerts
|

National Heart Foundation of Australia consensus statement on catheter ablation as a therapy for atrial fibrillation

Abstract: Atrial fibrillation (AF) is estimated to affect 1%-2% of the population. It is increasing in prevalence and is associated with excess mortality, considerable morbidity and hospitalisations. AF is responsible for a significant and growing societal financial burden. Catheter ablation is an increasingly used therapeutic strategy for the management of AF; however, some confusion exists among those caring for patients with this condition about the role and optimal use of ablative treatments for AF. Our aim in this … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 22 publications
0
8
0
Order By: Relevance
“…[ 2 ] At present, although there are a variety of options for the treatment of AF, such as antiarrhythmic medication, surgical ablation, and catheter ablation, [ 3 – 5 ] catheter ablation is used as the first-line therapy by doctors and patients, [ 6 , 7 ] and it is increasingly being chosen as a therapeutic strategy for AF. [ 8 ] It is well known that AF recurrence is very common after catheter ablation and may decrease the probability of long-term success. [ 9 ] Studies have reported that several factors are related to AF recurrence after catheter ablation, such as obstructive sleep apnea, hypertension, age, sex, and obesity.…”
Section: Introductionmentioning
confidence: 99%
“…[ 2 ] At present, although there are a variety of options for the treatment of AF, such as antiarrhythmic medication, surgical ablation, and catheter ablation, [ 3 – 5 ] catheter ablation is used as the first-line therapy by doctors and patients, [ 6 , 7 ] and it is increasingly being chosen as a therapeutic strategy for AF. [ 8 ] It is well known that AF recurrence is very common after catheter ablation and may decrease the probability of long-term success. [ 9 ] Studies have reported that several factors are related to AF recurrence after catheter ablation, such as obstructive sleep apnea, hypertension, age, sex, and obesity.…”
Section: Introductionmentioning
confidence: 99%
“…In addition to the CHADS 2 , the CHA 2 DS 2 -VASc acknowledges that stroke risk in patients with AF is related to age as a continuous variable, the higher risk of stroke in women, and incorporates risk associated with vascular disease, prior MI, complex aortic plaque, and peripheral arterial disease [18,20,22]. The CHA 2 DS 2 -VASc score states that antithrombotic therapy may be omitted for a score of 0, either oral anticoagulants, aspirin, or no antithrombotic therapy can be considered for a score of 1, and oral anticoagulation is recommended for patients with a prior stroke, TIA, or a score of 2 or more [3,9,15,16,18,20,[22][23][24][25][26]. Although CHADS 2 and CHA 2 DS 2 -VASc scores were useful tools in the past in assisting to quantify risk of stroke in patients with NVAF, recent studies have shown that the CHA 2 DS 2 -VASc score is only able to correctly predict strokes in approximately 68% of cases [3,18,22].…”
Section: Evaluation Of Embolic Riskmentioning
confidence: 99%
“…It has been shown, however, that patients with CKD and nonvalvular AF have a heightened stroke risk regardless of CHADS2DS2-VASc score, where 80% of patients having scores of ≥2 [29]. Current ACC/AHA/ESC guidelines advise that for a CHADS 2 score of ≥2 for either men or women, formal anticoagulation is recommended for patients [3,9,15,16,20,[22][23][24][25][26]30]. Those with a CHADS 2 score of 1, formal anticoagulation or aspirin alone should be considered in conjunction with patient specific comorbidities [3,9,15,16,20,[22][23][24][25][26].…”
Section: Anticoagulation Therapy In Atrial Fibrillationmentioning
confidence: 99%
See 2 more Smart Citations